2021
DOI: 10.3390/v13101970
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterizations and Molecular Evolution of the Measles Virus Genotype B3’s Hemagglutinin (H) Gene in the Elimination Era

Abstract: Measles virus (MeV) genotype B3 is one globally significant circulating genotype. Here, we present a systematic description of long-term evolutionary characterizations of the MeV genotype B3’s hemagglutinin (H) gene in the elimination era. Our results show that the B3 H gene can be divided into two main sub-genotypes, and the highest intra-genotypic diversity was observed in 2004. MeV genotype B3’s H gene diverged in 1976; its overall nucleotide substitution rate is estimated to be 5.697 × 10−4 substitutions/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
2
1
Order By: Relevance
“…Recent studies have shown that environmental filtering drives plankton community assembly at different seasons in rivers, estuaries and lakes that are highly disturbed by human activities (Isabwe et al, 2018;Zhou et al, 2021;Shen et al, 2022). However, our results indicated that phytoplankton assembly processes showed obvious seasonal change in the near-natural highland floodplain.…”
Section: Assembly Processes Of Phytoplankton Communities In River-oxb...contrasting
confidence: 66%
“…Recent studies have shown that environmental filtering drives plankton community assembly at different seasons in rivers, estuaries and lakes that are highly disturbed by human activities (Isabwe et al, 2018;Zhou et al, 2021;Shen et al, 2022). However, our results indicated that phytoplankton assembly processes showed obvious seasonal change in the near-natural highland floodplain.…”
Section: Assembly Processes Of Phytoplankton Communities In River-oxb...contrasting
confidence: 66%
“…dropped from 145 per million individuals to 18 per million individuals. Besides this, the current situation is that, this virus has re-surfaced, and its cases have been increased up to 25, 49, and 120 per million individuals, respectively from 2017 to 2019 (3). Additionally, the outbreaks of this virus have also monitored in the developed states with high acceptability of vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization's pursued objective of eliminating measles is exigent, and it still prevails as a primary public healthiness challenge for mankind. The postponement caused in pediatric vaccines as a repercussion of the COVID-19 contagion, might intensify viral transportation of both; measles and additional vaccine-avertable ailments (1, [3][4][5]. The eradication of measles eradication is achievable; however, serious commitment from all over the globe is necessary for sustaining long term developments to reduce measles mortality and morbidity trends along with achieving regional eradication objectives.…”
Section: Introductionmentioning
confidence: 99%